Extending MQTT-SN with Real-Time Communication Services - Fontes, Fernando (2022)
The Message Queuing Telemetry Transport (MQTT) protocol is one of the most popular application-layer protocols for machine-to-machine communications. Its popularity results from its simplicity and effective publisher/subscriber messaging model, which allows lightweight implementations able to run on resource constrained devices, thus making this protocol suitable for (Industrial) Internet of Things applications. However, MQTT's Quality-of-Service classes lack support for real-time services, impairing its adoption in applications where data exchanges are subject to timeliness requirements. This limitation was addressed in the literature, but contributions have been focused essentially on the broker software operation. This paper complements these works, presenting a comprehensive set of extensions to the MQTT protocol that aim at supporting real-time semantics and services at the network level. This paper presents the set of extensions as well as a preliminary proof-of-concept implementation, based on MQTT-SN. Preliminary results show the feasibility of the approach, being observed significant improvements on the traffic timeliness.